Sobre viver em Maceió: atos de vida de pessoas LGBTQIA+ em situação de rua na perspectiva da terapia ocupacional social - Silva, Rodrigo Gonçalves Lima Borges da (2023)
Introduction: The reality of homeless people living in marginality and precariousness is marked by poverty, survival process and resistance. This situation was aggravated as a result of the COVID-19 pandemic, which covered the worldwide territory. Considering the social markers of differences, the social issue, the social structure of hierarchies between individuals and social occupational therapy, it is relevant to understand the ways of life of different social groups, as well as homeless LGBTQIA+ people, in view of understanding multiple lives and survival, discussing professional actions with this population. Objective: To understand life moments of homeless LGBTQIA+ people during the COVID-19 pandemic, in Maceió/AL, Brazil. Methods: Starting from institutional spaces, as a "Consultório na Rua", a service of the Health Department of the City of Maceió, in Alagoas, and also from two non-governmental shelters for LGBTQIA+ people, we invited seven people to present us some of their lives through interviews, with data complemented by participant observation in the services and informal conversations. Results: The fields data demonstrated ruptures and creations of new social support networks, in processes that permeate social marginalization and precariousness. Going to the streets was described as a critical event caused by the rupture with the family, due to conflicts arising from the experience of a dissidence of gender and sexuality, marked in stories that go through poverty as a condition of life. From life on the streets, social institutions are important components of the social support network, permitting access to basic necessities, like food and a place to sleep. In this context, dreams are woven, at times as an escape from the precarious reality, at other times as the creation of possibilities and facing reality, mixing strategies for the maintenance of their lives, revealing how to live. The context of the pandemic aggravated the conditions for the maintenance of basic survival necessities, and all the collaborators of this study were already living on the streets when the pandemic started. Discussion: As a reading key for the results, "acts" were drawn, understood as moments of life that exist between the birth and death of the human being. The "acts" are a poetic way of reading reality to think strategies for professional action. They are: how to get together; how to exist; how to survive; about living in the pandemic; and time to dream, which present how to survive in Maceió, AL during the pandemic and the creative possibilities of life beyond marginalization and ruptures. Conclusion: To understand the ways of life through the proposition of "acts" configures itself as a possibility of understanding the ways of life of LGBTQIA+ people living on the streets, based on their narratives, which describe the possibilities of creating strategies for survival, as well as the living during the pandemic. The reflections on life moments through acts are expected to collaborate with new theoretical and conceptual perspectives for the development of professional actions, especially for occupational therapists, with this population.